A coordenação pedagógica como assessoria de formação continuada: o pensar e o agir na proposição de ações formativas na escola - MARTINS , Alexandrina Colins (2020)
PEDAGOGICAL COORDINATION AS CONTINUOUS professional development ADVISORY: thinking and acting in the provision of formative assessment at school, research developed in the professional master's degree, had the general objective of developing collaborative pedagogical intervention with the participating coordinators, through a continuous professional development training course for pedagogical coordinators of public schools in São Luís with a focus on the content ‘offering of continuous education for educational professionals', aiming at the elaboration of theoretical methodological guidelines, in order to provide formative assessment for schools, materialized in a booklet . To achieve our goals, we used the collaborative methodology, based on Ibiapina (2008, 2016), which enabled the participation of a group of pedagogical coordinators, who work in municipal public schools that are part of the SEMED Nucleus of São SEMED de São Luís. The theoretical background on the themes of Pedagogical Coordination and Continuing Education are based on the thoughts of authors such as: Almeida and Placco (2010); Canary (2004); Cruz (2017); Domingues (2014); Imbernón (2011); Libâneo (2004); Nóvoa (2001); Pepper (2015); Tardif (2012) 0 Saviani (2005); Vasconcellos (2002). The empirical data was produced during questionnaires and pedagogical meetings as research instruments. The applied diagnostic questionnaire carried out the generation of data, which originated the collaborative mediation, with the offer of the continuous formative education course for the pedagogical coordinators. The development of the respective course allowed us to bring out the final booklet entitled: Methodological itinerary for the provision of continuous professional development for teachers at school. The conclusions showed the relevance of the study, which provided the collaborators with the opportunity to acquire theoretical methodological elements when proposing formative assessment actions at school.